Roles and research trends of flipped classrooms in nursing education: a review of academic publications from 2010 to 2017. Issue 6 (18th August 2021) - Chung, Ching-Jung; Lai, Chiu-Lin; Hwang, Gwo-Jen
ABSTRACT: This study reviewed the published papers on the flipped classroom in nursing education from 2010 to 2017, and tabulated the collected data from various aspects: "before-class stage/ in-class stage/ after-class stage learning strategies, " "application domains, " "research issues, " "participants, " "research methods, " and "nationalities" based on a theoretical framework. It was found that basic level of flipped classroom mode was frequently used in nurse education; that is, guiding students to watch instructional videos before class, and conducted discussion or practicing in the class. On the other hand, several effective strategies, such as Mindtools and game-based learning, were seldom adopted; in addition, several important educational issues, such as learning behavior, were not investigated in flipped nursing education research. It was also found that most of the studies did not design after-class activities to engage students in organizing and applying what they had learned from multiple units in a project-based task. Accordingly, several suggestions for future studies are proposed.